2013
DOI: 10.15376/biores.9.1.906-921
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Physical Stability of Plasticized Hemicellulose Films

Abstract: aOat spelt arabinoxylan (OsAX) and spruce galactoglucomannan (GGM) are hemicelluloses that can be extracted in large quantities from sidestreams of the agriculture and forest industries. They both form selfstanding films, making them potential future packaging materials. This systematic study focuses on the effect of long-term storage on the physical stability of hemicellulose-based films. OsAX and GGM films were plasticized with 40% (w/w of the polysaccharide) of glycerol, sorbitol, or their blends, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In the current study, the WVP, tensile strength, and elongation at break of all film specimens decreased after storage at 5, 25, and 45°C for 30 days. These changes could possibly be attributed to the instability of the plasticizers (glycerol and/or sorbitol) due to plasticizer migration from the film matrix to the surface and the surrounding environment during storage time (Heikkinen et al., ; Osés et al., ). Storage time decreased the WVP and the elongation at break of all films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the WVP, tensile strength, and elongation at break of all film specimens decreased after storage at 5, 25, and 45°C for 30 days. These changes could possibly be attributed to the instability of the plasticizers (glycerol and/or sorbitol) due to plasticizer migration from the film matrix to the surface and the surrounding environment during storage time (Heikkinen et al., ; Osés et al., ). Storage time decreased the WVP and the elongation at break of all films.…”
Section: Resultsmentioning
confidence: 99%
“…Storage time decreased the WVP and the elongation at break of all films. It is indicated that plasticization and free volume in the film network were decreased after glycerol migration out of the film matrix (Heikkinen et al., ; Mikkonen et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the aging of GGM and AX films with 20–60% incorporated glycerol or sorbitol revealed interesting changes of the materials after 4 months. Elongation at break and water vapor permeability decreased and the strength and Young's modulus increased, while degree of crystallinity and oxygen barrier properties remained unaffected with time . These changes were suggested to be associated with the water content in the films.…”
Section: Applications Of Plant Polysaccharide Materials In the Packagmentioning
confidence: 93%
“…Food preservation is usually a long-term process, so the long-term stability of packaging is also important. When Susanna and co-workers [ 73 ] studied the plasticized film made from oat spelt arabinoxylan and spruce galactoglucomannan, they found that although the mechanical properties of the film slightly deteriorated after four months of use, water vapor permeability decreased significantly and oxygen permeability value changed little. Therefore, the barrier property of modified hemicellulose film will remain at a high level in the long term use.…”
Section: Application In Food Packagingmentioning
confidence: 99%